Pareceristas ad hoc (Tempo e Argumento, 2009)
Ana Luiza Setti Reckziegel, Universidade de Passo FundoAna Paula Vosne Martins, Universidade Federal do ParanáAntonio Emilio Morga, Universidade Federal do AmazonasAntônio Manoel Elíbio Júnior, Universidade do Sul de Santa CatarinaClarícia Otto, Universidade Federal de Santa CatarinaElisom Antônio Paim, Universidade Comunitária Regional de ChapecóGeni Rosa Duarte, Universidade do Oeste do ParanáJanine Gomes da Silva, Universidade da Região de JoinvilleJosé Roberto Severino, Universidade Regional de BlumenauMara Rúbia Sant’Anna, Universidade do Estado de Santa CatarinaMauríco Lissovsky, Universidade Federal do Rio de Janeiro